Isolation and characterization of a molybdenum-reducing and glyphosate-degrading klebsiella oxytoca strain saw-5 in soils from sarawak - Sabullah M.K.; Rahman M.F.; Ahmad S.A.; Sulaiman M.R.; Shukor M.S.; Shamaan N.A.; Shukor M.Y. (Agriculture Faculty Brawijaya University, 2024)
Indexed by WOS/ Scopus